ISOLATION OF ENDOPHYTIC FUNGI FROM PATCHOULI LEAVES (POGOSTEMON CABLIN BENTH) AS ANTIBACTERIAL AGAINST PATHOGENIC BACTERIA BY BIOAUTOGRAPHY AND AGAR DIFFUSION - Arif, Sitti Nur haerani (Fakultas Farmasi, Universitas Muslim Indonesia, 2023)
Patchouli (Pogostemon cablin Benth) is a plant used as a substance in the pharmaceutical industry such as the manufacture of anti-inflammatory, antifungal, anti-insect and anti-inflammatory drugs. This study aimed to obtain endophytic fungi isolates having the potential as antibacterial by using TLC- Bioautography and agar diffusion methods. This research was conducted by isolating the endophytic fungi from Patchouli leaves and after that, purification and macroscopic tests were carried out and ten isolates were obtained pure. The results of the isolate screening test with codes IFDN 1, IFDN 3, IFDN 4, IFDN 6, IFDN 7, IFDN 8 and IFDN 9, showed the highest inhibition. Furthermore, the antibacterial activity was assayed by TLC-Bioautography. The results showed active spots (Rf 3 = 0.54; Rf 4 = 0.61; Rf 6 = 0.58; Rf 7 = 0.45; Rf 8 = 0.54; Rf 9 =0.47) against Eschericia coli, Staphylococcus aureus and Staphylococcus epidemics. The results of the antibacterial activity test by diffusion method obtained an inhibition zone for each bacterium, namely Staphylococcus aureus of 8.66 mm, Staphylococcus epidermidis of 8.38 mm, and Eschericia coli of12.23 mm.Key Words: Agar diffusion; Antibacterial; Endophytic fungi; skin infections; TLC Bioautograph.